TWO DIFFERENT COLOUR MORPHS OF STIRETRUS DECEMGUTTATUS (LEPELETIER & SERVILLE, 1828) (HEMIPTERA: HETEROPTERA: PENTATOMIDAE: ASOPINAE) FEEDING AND MATING AT THE SAME TIME (Acta Entomologica Serbica, 2018)
On 02.12.2017, Oscar C. B. Neto was able to make an interesting observation in his backyard in Benedito Novo, Santa Catarina, Brazil: Two different colour morphs of Stiretrus decemguttatus could be photographed while they were mating and feeding at the same time (Fig. 1). One specimen was feeding on a larva, while the other one was feeding on an Asopine, probably another colour morph of S. decemguttatus or a specimen of S. erythrocephalus. Both species have similar blue colour patterns which differ in tibial expansions and median abdominal spine (Thomas, 1992), characters which are not visible in Figure 1.